Spatial Correlations and Distribution of Competence Gene Expression in Biofilms of Streptococcus mutans - Ishkov, Ivan P.; Kaspar, Justin R.; Hagen, Stephen J. (Frontiers in Microbiology, 2021)
Streptococcus mutans is an important pathogen in the human oral biofilm. It expresses virulent behaviors that are linked to its genetic competence regulon, which is controlled by comX. Expression of comX is modulated by two diffusible signaling peptides, denoted CSP and XIP, and by other environmental cues such as pH and oxidative stress. The sensitivity of S. mutans competence to environmental inputs that may vary on microscopic length scales raises the question of whether the biofilm environment creates microniches where competence and related phenotypes are concentrated, leading to spatial clustering of S. mutans virulence behaviors. We have used two-photon microscopy to characterize the spatial distribution of comX expression among individual S. mutans cells in biofilms. By analyzing correlations in comX activity, we test for spatial clustering that may suggest localized competence microenvironments. Our data indicate that both competence-signaling peptides diffuse efficiently through the biofilm. XIP elicits a population-wide response. CSP triggers a Poisson-like, spatially random comX response from a subpopulation of cells that is homogeneously dispersed. Our data indicate that competence microenvironments if they exist are small enough that the phenotypes of individual cells are not clustered or correlated to any greater extent than occurs in planktonic cultures.